The effect of temperature of the middle layer extracts of the ‏indigo acacia fruits on the treatment and absorption of the ‏resulting drugs in the human body - Ali , Abdalla Rayan (International Journal of Pharmacology and Toxicology, 2025)
After preparing the extract and conducting dilutions for the study, I took the ‎concentration of 100, which is the highest concentration, and conducted physical ‎tests on it, which consisted of detecting the temperature of the extract using a digital ‎thermometer. The temperature was prepared and measured under standard ‎conditions.We found that the temperature of the extract is 34.9 degrees Celsius, but ‎it is known from previous studies that the normal human temperature ranges ‎between (36.1, 37.2), which means that the temperature of the extract is lower than ‎the human temperature, i.e., it is endothermic. This means that it can be used as an ‎antipyretic for fever resulting from Staphylococcus aureus and other types, if the ‎reaction that occurs is endothermic, which adjusts the body temperature and ‎facilitates the process of absorption of the drug inside the body, which makes it ‎maintains its chemical composition. Vacuum chemistry accelerates the healing ‎process.